Staying Engaged in Terrorism: Narrative Accounts of Sustaining Participation in Violent Extremism - Ferguson, Neil; McAuley, James W. (Frontiers in Psychology, 2020)
Research exploring radicalization pathways and how and why people become involved in terrorism has expanded since the 9/11 attacks. Likewise, over the last decade research exploring de-radicalization and desistence from terrorism has grown and expanded in an attempt to promote exit from extremist or terror groups. However, research studies on how individuals sustain engagement in terrorism and their involvement with extremist organizations, often in the face of great adversity, are absent from the body of research. To address this scarcity of research this study analysed accounts of engagement in violent extremism produced by Northern Irish loyalist and republican paramilitaries in order to explore how their paramilitary lifestyle, perpetration of acts of political violence and the pressure from countering threats posed by rival groups, and the State security forces impacted on them. The analysis utilized a hybrid of thematic analysis and interpretative phenomenological analysis. The themes raised through the analysis reflected the psychological, social and economic hardship associated with this lifestyle. The narrative accounts also illustrated psychological changes associated to engagement in violence and from insulation within tightly knit extremist groups. As most of the participants faced incarceration during their paramilitary careers, themes also reflected on the impact imprisonment had on them. The themes explored factors that sustained their involvement, including the role of identity development and identity fusion in sustaining their extremism, the impact of insulated group membership, feelings of efficacy, dehumanization processes, community support and beliefs in the utility of violence.